Horticulture- Pruning - Frank Aston::::::photographer::: (1907)
Students pruning trees. This photo was printed in the 1916-1917 Course Catalog Bulletin, page 29, with the title "Practical Horticulture" and may have been part of the instruction in the course "Horticulture II Principles of Fruit Growing." Probably 1907-08 school year, with professor of botany and horticulture Ira Judson Condit standing. Likely to also include Jagat Bondhu Dev, Jogadish C Goswami, and Devendra N Guha, three students from India who were enrolled in a one-year special study program in agriculture in the 1907-08 school year.